Alterations in apical dendrite bundling in the somatosensory cortex of 5-HT3A receptor knockout mice - Laura A Smit_Rigter; Wytse J Wadman; Johannes A Van Hooft (Frontiers Media S.A., 2011)
In the cerebral cortex of various species, apical dendrites of pyramidal neurons form clusters which extend through several layers of the cortex also known as dendritic bundles. Previously, it has been shown that 5-HT3A receptor knockout mice show hypercomplex apical dendrites of cortical layer 2/3 pyramidal neurons, together with a reduction in reelin levels, a glycoprotein involved in cortical development. Other studies showed that in the mouse presubicular cortex, reelin is involved in the formation of vertical columnar structures. Here, we compare apical dendrite bundling in the somatosensory cortex of wildtype and 5-HT3A receptor knockout mice. Using a microtubule associated protein (MAP) 2 immunostaining to visualize apical dendrites of pyramidal neurons, we compared dendritic bundle properties of wildtype and 5-HT3A receptor knockout mice in tangential sections of the somatosensory cortex. A Voronoi tessellation was performed on immunostained tangential sections to determine the spatial organization of dendrites and dendritic bundles. In 5-HT3A receptor knockout mice, dendritic bundle surface was larger compared to wildtype mice, while the number and distribution of reelin-secreting Cajal-Retzius was similar for both groups. Together with previously observed differences in dendritic complexity of cortical layer 2/3 pyramidal neurons and cortical reelin levels, these results suggest an important role for the 5-HT3 receptor in determining the spatial organization of cortical connectivity in the mouse somatosensory cortex.